Land Degradation Controlled and Mitigated by Rubber‐based Agroforestry Systems through Optimizing Soil Physical Conditions and Water Supply Mechanisms: A Case Study in Xishuangbanna, China. (2nd August 2017) - Jiang, Xiao Jin; Liu, Wenjie; Wu, Junen; Wang, Pingyuan; Liu, Changan; Yuan, Zi‐Qiang
Abstract: Different rubber‐based agroforestry systems are adopted to control and mitigate land degradation. However, the soil physical conditions and soil hydrological processes of different agroforestry systems are still unclear. Thus, in this study, rubber ( Hevea brasiliensis ) monoculture, rubber and Clerodendranthus spicatus agroforestry system (RCS) and rubber and Amomum villosum agroforestry system (RAV) were developed from a degraded land that had similar backgrounds of terrain and management measures for 50 years. Conventional methods were applied, and dye tracer experiments were conducted to measure the soil physical conditions and determine the water movement in soil. After 5 years' growth, both RCS and RAV could effectively promote the soil physical conditions and optimize soil structure by improving the proportion of the three soil phases. Favourable soil properties, multiple‐layered canopies and ground cover in agroforestry systems could promote the formation of three‐dimensional hydraulic redistribution in soil profile. The infiltration of rainfall into the soil was enhanced; meanwhile, surface runoff and soil erosion were mitigated, and then more water was transported, redistributed and stored into the different soil layers by the more dominant preferential flow, water exchange and lateral flow in soil profiles. These water supply mechanisms could allow planting intercrops with rubber trees to uptake water from different water sources and coexist in an agroforestry system. Our results highlighted that rubber‐based agroforestry systems are a useful management practice to maximize the utilization of land and water resources. Copyright © 2017 John Wiley & Sons, Ltd.